Non invasive prenatal diagnosis of fetal aneuploidy using cell free fetal DNA. (June 2018) - Renga, Barbara
Abstract: The discovery of cell free fetal DNA in maternal plasma has stimulated a rapid development of non-invasive prenatal testing. The recent advent of massively parallel sequencing has allowed the analysis of circulating cell-free fetal DNA to be performed with unprecedented sensitivity and precision. It is thus expected that plasma DNA-based non invasive prenatal testing will play an increasingly important role in the future of obstetric care. The present review summarizes recent advances in non invasive prenatal testing using cell free fetal DNA. The importance of genetic counseling, the current guidelines for the use of cffDNA screening in pregnancy, as well as specific maternal conditions that can affect the performance of non invasive prenatal testing are also discussed in this review.